Treatment of the Neuroleptic Malignant Syndrome in International Therapy Guidelines: A Comparative Analysis - Schönfeldt-Lecuona, Carlos; Kuhlwilm, Lilli; Cronemeyer, Maximilian; Neu, Peter; Connemann, Bernhard J.; Gahr, Maximilian; Sartorius, Alexander; Mühlbauer, Viktoria (Pharmacopsychiatry, 2020)
Introduction The neuroleptic malignant syndrome (NMS) is a potentially life-threatening condition associated to the use of antipsychotics. Since it requires rapid and efficient medical care, high-quality treatment guidelines should be available. In this article, we analyzed and compared different international therapy guidelines for the treatment of schizophrenia, in which NMS treatment recommendations might be contained.Methods We performed an Internet-based search for schizophrenia guidelines via the website of the respective medical society. Guidelines in English, French, Italian, and German from countries whose medical care meets high standards were selected for further analysis and comparison of the NMS treatment recommendations (if present), and their underlying evidence.Results The NMS is mentioned in 12 of 14 guidelines. Only 9 report concrete therapy recommendations (benzodiazepines/dantrolene/bromocriptine/amantadine/intensive care and/or electroconvulsive therapy (ECT)), however, with high heterogeneity. Only 5 guidelines included all possible drug therapy options and ECT, but with differing combination strategies, dosages, application forms, and combinability of options. The level of evidence of the different recommendations was estimated as low.Discussion One-third of the selected guidelines do not report any NMS therapy recommendations. Most guidelines mentioning the NMS do not provide therapy recommendations that include all relevant treatment options. The results show a very high heterogeneity, and the recommendations and statements are of low-evidence levels. The lack of knowledge about the NMS and its treatment may delay the onset of therapy, impair the quality of treatment, and lead to a worse outcome or death.
Keywords: neuroleptic malignant syndrome; guideline; treatment; antipsychotics; adverse reaction